Higher Body Mass Index and Waist Cicumference Have Correlation With the degree of Curvature of Hyperlordosis in Young Adult - Fitriani Rahmawati; Nuryani Sidarta (Indonesian Journal of Physical Medicine & Rehabilitation, 2016)
BACKGROUND : Health problem that caused by higher BMI have grown broadly. Musculoskeletaldisorders due to higher BMI will cause an excessive burden on the lumbosacral joints. .Moreover, excess waistcircumference can also lead to malformation of lumbal curvature.Purpose: This study aims to determine the relationship between higher Body Mass Index (BMI) and excesswaist circumference with the higher curvature in young adult.Method: This study used observational study with cross-sectional design involving 88 students whoperformed measurement of body weight, height, and waist circumfrences, also lumbar curve examination. Themeasurement of waist circumference was done by circling the flexible tape on waist. For the measurement ofthe lumbar curve,each respondent is measured by a flexible ruler.Results: chi square test obtained p = 0,000 in high BMI with the increasing of lumbar curve and p = 0,000 inexcess waist circumference with the increasing of lumbar curve. So, there is a correlation between higher BMIand excess waist circumference with the increase of lumbar curve in the young adults.Conclusions: In this study showed that higher BMI and excess waist circumference have correlation with theincrease of lumbar curve in the students.Keywords: body mass index, waist circumference, tape measure, hyperlordosis, flexible ruler.